2015
DOI: 10.1007/s11595-015-1204-8
|View full text |Cite
|
Sign up to set email alerts
|

Influence of various materials on biomechanical behavior of endocrown-restored, endodontically-treated mandibular first molar: A 3D-finite element analysis

Abstract: To evaluate the effect of restorative materials on stress distribution of endodontically treated teeth, the 3D models of an endodontically treated mandibular fi rst molar, restoration, and cement layer were created. Three different materials (composite resin, ceramage and ceramic) were studied and two loading conditions (vertical and oblique load) were simulated. Mohr-Coulomb failure criterion of enamel, dentine, endocrown and cement were evaluated separately. It is indicated that under both loading conditions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 20 publications
0
10
0
Order By: Relevance
“…Endocrown eliminate the need for posts and build up therefore they are less expensive, time saving and more practical (10) . Endocrowns were presented as a prosthetic treatment to restore root canal treated incisors (24) , premolars (25) and molars (26,27) with great tissue loss. The endo-core improves the bonding surface of restorations inside the root in addition to their macromechanical retention, decreasing their displacement from the root cavity under lateral stresses (28) .…”
Section: Discussionmentioning
confidence: 99%
“…Endocrown eliminate the need for posts and build up therefore they are less expensive, time saving and more practical (10) . Endocrowns were presented as a prosthetic treatment to restore root canal treated incisors (24) , premolars (25) and molars (26,27) with great tissue loss. The endo-core improves the bonding surface of restorations inside the root in addition to their macromechanical retention, decreasing their displacement from the root cavity under lateral stresses (28) .…”
Section: Discussionmentioning
confidence: 99%
“…It was concluded that endocrowns had highest number of repairable fractures. Paradigm MZ100 Chen et al 31 Evaluation of influence of restoration material used on stress distribution of endocrown restorations of endodontically treated mandibular first molar teeth under vertical and oblique simulated by finite element stress analysis.…”
Section: Ips Empress Cadmentioning
confidence: 99%
“…24 Studies evaluating the CAD/CAM restorations fabricated with different materials and techniques are presented in Table II. [25][26][27][28][29][30][31] It was concluded that for ceramic onlays proximal box elevation had no effect on either marginal integrity or fracture behavior. In terms of marginal integrity and fracture resistance composite onlays were found to be superior to ceramic onlays, specially in specimens without proximal box elevation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such high failure rate can be associated with the lack of understanding of natural tooth structure and its behaviour under external loading. The artificial crowns are designed to have physical material properties similar or higher than those of the natural enamel, the hardest and stiffest material in the human body, unlike a multi-layered multi-stiffness natural tooth [13][14][15][16][17][18][19][20][21][22][23][24]. One of the periodontal ligamental connects the tooth to the mandibular bone and helps tooth movement [25].…”
Section: Introductionmentioning
confidence: 99%